Cattle veterinarians' awareness and understanding of biosecurity - Pritchard, K.; Wapenaar, Wendela; Brennan, Marnie L. (BMJ Publishing Group, 2015)
PREVENTIVE biosecurity measures, such as isolation of purchased animals, are well documented in the literature (Duncan 1990, Maunsell and Donovan 2008, Noremark and others 2009) and biosecurity has been highlighted as a key intervention for many of the important diseases affecting cattle in the UK (Scott 2013). There is evidence that not many practices are being undertaken by producers and various explanations have been suggested (Nerlich and Wright 2006, Brennan and Christley 2012, Brennan and Christley 2013). In comparison, there is limited literature on cattle veterinarians’ knowledge and opinions about biosecurity. There has been debate in previous studies as to whether biosecurity advice is being given by veterinarians and whether they feel qualified, or sure about what to advise (Gunn and others 2008, Jansen and Lam 2012). Therefore, the aim of this study was to determine the understanding and awareness of current on-farm biosecurity practices among cattle veterinarians in the UK.